Retraction of the article: Muraviev Yu., Gridneva G. Herpes zoster in RA patient treated with methotrexat - article Editorial (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Retracted article: Muraviev Yu., Gridneva G. Herpes Zoster in RA Patient treated with Methotrexate. Safety and Risk of Pharmacotherapy. 2014;(4):18-22. (In Russ.)This article by Muraviev Yu., Gridneva G. has been retracted (i.e. withdrawn from the press) by the editorial staff of Safety and Risk of Pharmacotherapy as a duplicate of the following publication: Muraviev Yu., Gridneva G. Herpes Zoster in RA Patient treated with Methotrexate. Safety and Risk of Pharmacotherapy. 2014;(1):27-30 (In Russ.)The Editorial board would like to extend their sincere apologies for any inconvenience this retraction may have caused.Minutes of the meeting of the Editorial Board of the journal Safety and Risk of Pharmacotherapy No. 2 of April 21, 2022.